Development Of A Vehicle Routing Problem Model To Reduce Service Delays In Pickup And Delivery Operations - Gilbert Stefhen; Dedy Suryadi; Titi Iswari (Journal of Social Research, 2025)
The rapid growth of the e-commerce sector in Indonesia has increased the demand for reliable and timely logistics services. However, challenges such as delayed pickups and deliveries continue to occur, leading to the accumulation of operational penalties. This study aims to develop a mathematical model based on the Vehicle Routing Problem (VRP) that addresses the complexities of modern logistics distribution. The proposed model, named HFMTVRPDPTW (Heterogeneous Fleet Multi-Trip Vehicle Routing Problem with Delivery and Pickup and Time Windows), incorporates five key elements: vehicle capacity, fleet heterogeneity, service time windows, simultaneous pickup and delivery, and multi-trip operations within a single working period. A systematic literature review of twenty-one prior studies was conducted to identify research gaps and inform the model’s development. The model is formulated using an integer linear programming (ILP) approach and aims to optimize service time accuracy while minimizing delays. The findings suggest that this model provides a more comprehensive and realistic approach to distribution challenges and offers an original contribution to the development of adaptive and efficient VRP models for logistics operations.